The fire break in Bialowieza national park as a refuge of the segetal flora - Bomanowska, A.; Adamowski, W. (Український ботанічний журнал, 2013)
Taking into account the extensive scale of farmland abandonment in the area of the Bialowieza Primeval Forest, the authors decided to investigate the flora of the fire break in Bialowieza National Park as potential refuge for segetal flora. One hundred and thirty-six plant taxa have been found to occur on the fire break, including 101 common to the segetal flora of the Biaіowiea Clearing. The most widespread species are Anthemis arvensis, Juncus bufonius and Scleranthus annuus; the most interesting are Peplis portula and Ranunculus sardous, formerly growing in wet furrows. Our results show that the ploughed fire break could be a refuge for segetal flora.